Characteristic Test Of Transistor Based Multisim Software - Muhammad Ruswandi Djalal; Herman HR (PROtek : Jurnal Ilmiah Teknik Elektro, 2019)
Abstract--The purpose of this study is to determine the characteristics of the transistor before it is used in the circuit. Transistors are semiconductor devices used as amplifiers, as circuit breakers and connectors (switching), voltage stabilization, signal modulation or as other functions. Transistor performance can be seen by testing input-output characteristics. Multisim is an electronic capture and schematic simulation program that is part of a series of circuit design programs, together with NI Ultiboard. Multisim can properly simulate electronic components.Â Â